Land, labour and diet in Northern Rhodesia : an economic study of the Bemba tribe - Richards, Audrey I. (Audrey Isabel), 1899-1984 (Published for the International Institute of African Languages & Cultures by the Oxford University Press, 1939)
Zambia, Ethnology, Anthropology, Social anthropology, Economics, Food, Agriculture, Nutrition.